2015
DOI: 10.1159/000374056
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of MiR-1294 is Related to Dismal Prognosis of Patients with Esophageal Squamous Cell Carcinoma through Elevating C-MYC Expression

Abstract: Aims: Changes in the expression of microRNAs (miRNAs) have been found in many cancers. This study aimed to investigate the expression of miR-1294 in patients with esophageal squamous cell carcinoma (ESCC) and its effect on prognosis. The underlying mechanism was explored as well. Methods: We examined the expression of miRNA in human ESCC cancer tissues and adjacent non-tumor controls using quantitative reverse transcription polymerase chain reaction (qRT-PCR). And the relationship between expressions of miR-12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 14 publications
1
30
0
Order By: Relevance
“…The cell proliferation was detected using MTT assay as described previously [14]. Briefly, the transfected SCC-4 cells were seeded in a 96-well plate.…”
Section: Methodsmentioning
confidence: 99%
“…The cell proliferation was detected using MTT assay as described previously [14]. Briefly, the transfected SCC-4 cells were seeded in a 96-well plate.…”
Section: Methodsmentioning
confidence: 99%
“…Oesophageal squamous cell carcinoma (ESCC) is one of the most common malignancy worldwide and is the most common subtype of oesophageal cancer in Asian countries [1][2]. miRNAs (19)(20)(21)(22)(23)(24)(25) nucleotides non-coding single stranded RNA) could play a critical role in the regulation of pathogenesis of the oesophageal cancer by regulating the expression of growth related target genes [3][4][5][6]. MicroRNA-498 (miR-498) is located intergenically in 19q13.42 and play critical roles in the pathogenesis of different carcinomas including colorectal, breast, lung, ovarian and thyroid as well as in acute myeloid leukaemia and Kaposi's sarcoma [7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been demonstrated that the miRNA profile of tissues exhibits characteristic changes in certain types of tumors [19,20]. A number of miRNAs have been shown to participate in tumor progression, invasion, and metastasis, including miR-134 [21], miR-145 [22], miR-625 [23], and miR1294 [24]. However, due to clinical heterogeneity, sample insufficiency, and use of various data processing methods, there is inconsistency in the results of these studies.…”
Section: Discussionmentioning
confidence: 99%